On the sequential point estimation of the powers of the ratio of two exponential scale parameters. - Largo, Fe F. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2015)
A fully sequential procedure is considered in the point estimation of the powers of the ratio of two exponential scale parameters. Formulation of the stopping rule is developed with the aim of minimizing the risk involved in the estimation of the parameter 0. Results of this paper show that the sampling scheme developed will eventually stop. In addition, first-order properties of the proposed sequential procedure are derived andsimulations usng Scilab are provided to give illustration of the performance of the proposed procedure.